PEMETAAN MUTU PAUD FULLDAY UNTUK MENINGKATKAN KUALITAS LAYANAN DAN KELEMBAGAAN PROGRAM PAUD - Puji Yanti Fauziah; Sugito Sugito (Graduate School, Universitas Negeri Yogyakarta, 2016)
Penelitian ini bertujuan untuk: (1) memetakan Program PAUD fullday; (2) menghasilkan rekomendasi penyelenggaraan PAUD fullday. Metode yang digunakan dalam penelitian ini adalah survei. Penentuan lembaga yang dijadikan sampel dilakukan secara acak sejumlah 23 lembaga se-DIY. Adapun hasil penelitiannya: 1) Standar pencapaian perkembangan anak sudah baik tetapi hasil capaian perkembangan baru hasil observasi dan penilaian kegiatan pagi sampai siang dan belum dilakukan terintegrasi dan holistik sepanjang hari; (2) rekomendasi dalam penyelenggaraan Program PAUD fullday adalah: (a) diperlukan kurikulum model pembelajaran yang holistik dalam arti menstimulasi seluruh aspek perkembangan anak dari pagi sampai sore; (b) diperlukan model penilaian yang integratif dari pagi sampai sore dari keseluruhan aktivitas anak, dan (c) pentingnya pemberdayaan orang tua dalam pembelajaran fullday dan lembaga telah melakukan pemberdayaan dengan baik.Kata kunci: PAUD fullday, kualitas layanan dan kelembagaan THE QUALITY MAPPING OF FULL DAY ECD FOR IMPROVING THE QUALITY OF SERVICE AND INSTITUTIONAL PROGRAMS ECDAbstractThis research aims to: (1) mapping the full day early childhood program; (2) Recommendation implementation of full day early childhood education. The method used in this research is the survey. Determination institution randomized sample number 23 taken from the early childhood institutions throughout the District. The description of the implementation of full day early childhood are: 1 Achievement standard child development has been good but the results of the achievements of the new developments on the observation and assessment of activities in the morning until noon, has not carried out an integrated and holistic throughout the day. recommendations for the implementation of full day early childhood program; (a) required a holistic learning model in the sense of stimulating all aspects of child development from morning till evening; (b) assessment of the achievement of the child’s development has not been documented in a neat necessitating a thorough assessment model of the overall activity of the child; (c) the importance of empowering parents in a full day of learning , and institutions have to empower parents with the goodKeywords: full day early childhood , quality of service and institutional